Determining the cultural safety of chronic disease interventions for Aboriginal and Torres Strait Islander Australians: a scoping review - Woodall, Hannah; Larkins, Sarah; Pinidiyapathirage, Janani; Ward, Raelene; Evans, Rebecca (Frontiers in Public Health, 2025)
ObjectivesTo assess how the cultural safety of primary care-based chronic disease interventions for Aboriginal and Torres Strait Islander Australians is determined.MethodsScoping review of peer-reviewed evaluations of chronic disease interventions for Aboriginal and Torres Strait Islander patients, in which cultural safety is an outcome. Searches included Scopus, Informit, OVID Medline, Emcare and CINAHL including all articles published until September 2023.ResultsSearches identified 2,225 articles. 1,854 articles underwent title and abstract screening, with 97 progressing to full text review. Twenty articles met the inclusion criteria. 75% (n = 15) of articles determined cultural safety based solely on Aboriginal and Torres Strait Islander peoples’ perspectives, with community acceptance as the most common means of determining cultural safety. In the analysed studies, elements contributing to cultural safety included practitioner behaviour (n = 15), knowledge (n = 6), skills (n = 1) and attitudes (n = 4), partnership with community (n = 4) and culturally safe services (n = 5), and graphics and artwork (n = 6). The inconsistent terminology and lack of definitions made comparison of studies challenging.ConclusionThis review underscores the importance of adopting the Australian Health Practitioner Regulation Agency (AHPRA) definition of cultural safety to standardise terminology and explore the many elements of cultural safety. It is recommended that cultural safety is defined by the community targeted by the intervention. Identification of elements of cultural safety will guide future interventions and reduce reliance on community acceptance as an indirect measure of cultural safety. If chronic diseases interventions are to effectively impact health equity, it is vital to understand cultural safety within these settings.